2021
DOI: 10.1002/ajp.23343
|View full text |Cite
|
Sign up to set email alerts
|

Do chimpanzees enjoy a virtual forest? A pilot investigation of the use of interactive art as a form of environmental enrichment for zoo‐housed chimpanzees

Abstract: Environmental enrichment is essential for the well-being of zoo animals. Recent advances in sensor and video technologies may contribute to improvements in enrichment in terms of their flexibilities and time constraints. The purpose of this study was to investigate whether interactive movie art can be used as a form of environmental enrichment. We implemented interactive movies designed by a professional artist, a visual art aiming to reflect naturalistic forest habitat, in an indoor chimpanzee enclosure at Ky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In general, we found that our ethograms were effective in capturing the range of enrichment objects, manipulation behaviors, and social contexts observed in our sample. Enrichment studies tend to investigate one form or category of enrichment [ 11 , 13 , 17 , 23 , 24 ] rather than multiple enrichment categories simultaneously [ 12 ]. The current findings indicate that captive chimpanzees will voluntarily interact with a wide variety of objects when available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, we found that our ethograms were effective in capturing the range of enrichment objects, manipulation behaviors, and social contexts observed in our sample. Enrichment studies tend to investigate one form or category of enrichment [ 11 , 13 , 17 , 23 , 24 ] rather than multiple enrichment categories simultaneously [ 12 ]. The current findings indicate that captive chimpanzees will voluntarily interact with a wide variety of objects when available.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while neither social interactions nor aggressivity have been shown to vary in relation to the number of enrichment objects present [ 9 ], how those objects were used in larger social contexts was not examined. It is also rare for studies to categorize a wide range of device types, with studies often measuring behaviors in relation to only one type or category of enrichment (e.g., [ 11 , 13 , 17 , 23 , 24 ]). This is unfortunate given that, to fully understand how enrichment objects are used in social settings, it may be necessary to introduce and investigate a wide range of enrichment object categories.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the growing field of animal-computer interaction (ACI), which emphasizes iterative user-centric design processes and consent on the part of the animal [24], has spawned a variety of projects that use electronics as an enrichment for primates, often without the practice of provisioning food rewards. Efforts along these lines include systems involving projection screens and sensors at Kyoto City Zoo [25] and Melbourne Zoo [26] to create immersive interactive activities for great apes, and touchscreen-based musical, video, and puzzle apps for orangutans at Zoo Atlanta on a screen embedded in a large fake tree in their enclosure [27]. Giving primates choice and control over environmental factors has also been investigated in a study with white-faced sakis using proximity sensors to activate different sounds and videos in their enclosure [28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, zoos from America (e.g., Martin & Shumaker, 2022;Vonk, 2022), Europe (e.g., Laméris et al, 2022;Spiezio et al, undefined 2022), and Asia (e.g., Yamanashi et al, 2022) are represented, reflecting the global interest in zoo-based primatological research (Hopper, 2017).…”
mentioning
confidence: 99%
“…for this special issue I wanted to invite contributions from researchers studying zoo-housed monkeys and prosimians (e.g., Cairo-Evans et al, 2022;Hayden et al, 2022;Spiezio et al, 2022) in addition to those studying apes (e.g., Laméris et al, 2022;Martin & Shumaker, 2022;Motes-Rodrigo & Tennie, 2022;Vonk, 2022;Yamanashi et al, 2022).…”
mentioning
confidence: 99%